Problematyka wielowymiarowych drzew klasyfikacyjnych - Kurzydłowski, Adam (Multivariate classification trees problems, 2006)
Classification trees belong to the group of the exploration methods, exploited in searching and detecting relations occurring in the data. In the article a classification multivariate trees problems is presented. Multivariate trees classify examples by testing linear combinations of the variables at each non-leaf node of the tree.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (13); 2006; nr 1126, s. 501-509